Assessment of five global gridded precipitation estimates over a southern Mediterranean basin (Tensift, Morocco) - Kaoutar Oukaddour; Younes Fakir; Michel Le Page (Geomatics, Natural Hazards & Risk)
Gridded Precipitation Products (GPPs) could exhibit discrepancies related to detecting precipitation amounts and patterns. This paper aims to evaluate the accuracy of five GPPs currently in operational production over the Tensift basin in the southern Mediterranean. The GPPs are reanalysis-based (ERA5, ERA5-Land, MERRA-2) and multi-source data fusion (TerraClimate, MSWEPv2.8). Their annual and monthly precipitation are compared to observations from fourteen ground gauges over the entire period from 1980 to 2021 and each decade of this period. A set of statistical metrics, such as the Kling Gupta Efficiency (KGE) and the Root Mean Square Error (RMSE), as well as the Bias, served to carry out the evaluation. Four main findings could be highlighted: (i) GPPs have, in general, a good correlation with gauge data; hence they could be used to study the temporal variability of the observed annual and monthly precipitation. (ii) ERA5-Land does not bring significant improvements in precipitation estimates apart from its finer spatial resolution. (iii) GPPs perform better in the plain than in the mountains. (iv) TerraClimate and MSWEPv2.8 present better consistency across the decades. ERA5 and TerraClimate, the longest data series, were used to visualize the precipitation trends in the basin.